Hierarchical Supramolecular Assembly of Sterically Demanding π‐Systems by Conjugation with Oligoprolines1. Issue 46 (10th October 2014) - Lewandowska, Urszula; Zajaczkowski, Wojciech; Chen, Long; Bouillière, Francelin; Wang, Dapeng; Koynov, Kaloian; Pisula, Wojciech; Müllen, Klaus; Wennemers, Helma
Abstract Self‐assembly from flexible worm‐like threads via bundles of rigid fibers to nanosheets and nanotubes was achieved by covalent conjugation of perylene monoimide (PMI) chromophores with oligoprolines of increasing length. Whereas the chromophoric π‐system and the peptidic building block do not self‐aggregate, the covalent conjugates furnish well‐ordered supramolecular structures with a common wall/fiber thickness. Their morphology is controlled by the number of repeat units and can be tuned by seemingly subtle structural modifications.